Utilization of Black Soldier Fly Larvae in Processing Expired Food Waste with Various Composition - Yunita, Silma Maya; Siwiendrayanti, Arum; Nurjanah, Nurjanah (Universitas Diponegoro, 2024)
The study aimed to evaluate the effectiveness of Black Soldier Fly (BSF) larvae in processing expired food waste with different compositions, including expired instant noodles, bread, and milk, compared to a cassava pulp control. A true experimental design using a Posttest Only Control Group and Complete Random Design was employed. Over 15 days, temperature, pH, moisture, and waste reduction were measured. The results indicated that BSF larvae were most effective in reducing waste when fed expired instant noodles, with a Waste Reduction Index (WRI) of 5.68%, followed by bread (5.61%) and milk (5.47%). The lowest WRI was observed in the cassava pulp control group (5.28%). Statistical analysis using One Way ANOVA showed significant differences in WRI values among the waste compositions, confirming that BSF larvae efficiently reduce organic waste, particularly expired food, offering a sustainable solution for waste management.